الدواجن بين الإنتاج والتسويق في منشأة دواجن فديو في اللاذقية - الجوجو, نبيل (Latakia University Journal -Biological Sciences Series, 2018)
لقد خلصت الدراسة إلى النتائج التالية: 1. تراوح معدل التكلفة في المنشأة بين / 85.9 – 94.1 / ل.س نفقات لكل 100 ل.س إيرادات بالنسبة لقسم البياض ، وهذا يعني وجود هامش ربح منخفض خلال فترة الدراسة . 2. تراوح معدل التكلفة في المنشأة بين / 111.7 – 133.7 / ل.س نفقات لكل 100 ل.س إيرادات بالنسبة لقسم الفروج ، وهذا يعني أن النفقات تفوق الواردات ، وأن هناك خسارة خلال فترة الدراسة / 1999 – 2004 / لكنها بدأت فعلياً منذ مطلع التسعينات بسبب وجود ظروف موضوعية خارجية. 3. بلغت تكلفة الكيلو غرام الواحد من الفروج حوالي/ 81.89/ ل.س في عام 2004 وهي تكلفة عالية سببت الخسائر المذكورة أعلاه ، بينما كانت تكلفة البيضة الواحدة حوالي/ 2.34/ ل.س وهي تكلفة مرتفعة إلا أن أسعار بيض المائدة في السوق مرتفعة بحيث غطت التكاليف مع وجود هامش ربح محدود . 4. نظراً لعدم وجود أنفلونزا الطيور في سورية، ينتظر بأن تعمل المنشأة مستقبلاً بكامل طاقتها الإنتاجية. وفي الختام تم وضع التوصيات والمقترحات المناسبة التي من شأنها تطوير عمل منشأة دواجن فديو على أسس أكثر اقتصادية في المستقبل. The study has reached the following conclusions: 1.The average cost of eggs in the establishment ranged between /85.9/ and /94.1/ s.p. That meant it had a low marginal return during the study period. 2.The average cost of chicken in the establishment ranged between /111.7/ and /133.7/ s.p. That means that the expenses outweighed the revenues. There were losses during the study period between 1999 and 2004, but these losses had actually occurred in the early nineties due to objective and external circumstances. 3.In 2004, the cost of one kilogram of chicken was approximately /81.89/ s.p. This was a high cost and caused the above mentioned losses. Meanwhile the cost of one egg was approximately /2.34/ s.p. This was a high cost but the price of eggs in the market was high so that it covered costs and had a limited marginal return. 4.It is expected that the establishment will work in full capacity in the future since Syria is free from the bird flue virus. In conclusion, a set of recommendations and suggestions were given to develop Fedio Poultry Establishment in all aspects and in order for it to work on improving its financial planning in the Future.